Feasibility of Bio-Coal Production from Hydrothermal Carbonization (HTC) Technology Using Food Waste in Malaysia - Singh, A. (MDPI, 2022)
The alarming rise of food waste all over the world due to population and economic growth must be tackled with better waste management and treatment methods. The current practice of landfilling has been scientifically proven to adversely impact environmental and societal health. A relatively new technology called hydrothermal carbonization (HTC) has the potential to solve this problem. It takes in high-moisture-content material, like food waste, and converts it into bio-coal with a heating value similar to normal coal. The present study explored the feasibility of HTC technology and bio-coal production in Malaysia. An in-depth study via desk research was conducted by implementing Porterâs five forces analysis to evaluate the feasibility of the bio-coal production project. A survey involving 215 respondents from different households that represent the average demography of Malaysia was also conducted to understand the behaviors and attitudes of different households towards food waste. The present study found that a typical Malaysian household disposes mostly of meal leftovers, with an average of 926 g of food waste per day. In addition, the 3 highest food categories that were disposed of were rice or noodles or pasta (13.0), vegetables (12.2) and curry and soup (10.1). Meal leftovers such as curry and soup are high in moisture content, which is suitable for HTC. The survey on household waste provided adequate information to support the availability of a sufficient quantity of food waste in the country to sustain the raw material for the bio-coal project in Malaysia. Furthermore, a consumer survey involving seven industrial firms was conducted to determine the potential buyers of bio-coal. The responses from the industrial firms show that a bio-alternative for coal is important, and they are willing to transition to greener technologies. However, five out of seven firms stated that the main hurdle in adopting bio-coal is the high cost of production and incompatibility with existing industrial processes. Finally, interviews were conducted with key players in the industry to evaluate the adoptability of bio-coal into the wider market. The findings from the desk research and the primary research show that the outlook for bio-coal in the market is quite positive. In the long run, HTC is certainly profitable, but for immediate benefits, adequate government support and policy in favour of the use of HTC bio-coal in power plants are required. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.